A historical data analysis of water‐energy nexus in the past 30 years urbanization of Wuxi city, China. Issue 1 (21st September 2017) - Xie, Xinghua; Jia, Benyou; Han, Guoyi; Wu, Shiqiang; Dai, Jiangyu; Weinberg, Josh
Abstract : In this article, the historical data of water and energy consumption of Wuxi City, one of the main cities in the Taihu Lake Basin region in Eastern China, was reviewed and analyzed to map their dynamic changes in the rapid urbanization process of the past 30 years, as the urbanization ratio changed from 24.7% (1983) to 73.7% (2013). Results show that (a) water and energy resources have generally been managed separately in overall social‐economic development planning of the city and region; and (b) the increase of water and energy consumption closely correlates with the rate of urbanization and urban growth. A Water‐Energy Nexus Chart (WENC) is proposed as a potential tool to provide a snapshot on water and energy management to show relative efficiency of water use in energy production and energy use in water treatment and supply provision. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 46–55, 2018